Combined stereotactic radiation therapy and immunotherapy for metastatic uveal melanoma - Nazarova, Valeria V.; Orlova, Kristina V.; Magomedova, Zakhra R.; Romanov, Denis S.; Maskalenka, Raman; Yarovoy, Andrey A.; Yarovaya, Vera A.; Trofimova, Oxana P.; Shubina, Irina Zh.; Demidov, Lev V. (Frontiers in Oncology, 2025)
AimUveal melanoma (UM) is a rare primary intraocular malignant tumor with an extremely poor prognosis. Our study evaluated the feasibility to improve metastatic UM treatment outcomes with a combined approach of immunotherapy and radiation therapy.MethodsThe retrospective study enrolled 24 patients with metastatic uveal melanoma who had combined treatment with stereotactic radiation therapy (RT) and immune checkpoint inhibitor therapy. 35% of patients received combination immunotherapy, and the others received mono-immunotherapy with anti-PD-1 drugs. All patients underwent stereotactic RT for metastases in the liver (75% patients), bones (8%), soft tissues (8%), brain (4%), and lungs (4%).ResultsOverall response rate (ORR) was 39.1%. Complete response (CR) was achieved in 8.7% patients and partial response (PR) – in 30.4% patients, median progression free survival (PFS) was 11.6 months [95% confidence interval (CI), 5.4-14.4], and median overall survival (OS) was 27.6 months [95% CI, 16.9 - 49.1].ConclusionsThe study has demonstrated a safe combination of stereotactic radiation therapy and immune checkpoint inhibitor immunotherapy in patients with metastatic uveal melanoma. The combination shows a potential treatment option for this patient cohort since no other effective therapies are available at present.